Proceedings of the Statistical and Social Inquiry Society of Ireland: one hundred and sixty-second session: 2008/2009 - SSISI (Statistical and Social Inquiry Society of Ireland, 2009)
The first meeting of the Society was held at 6:00pm on Thursday 2nd October 2008 in the Royal Irish Academy, Dawson Street, Dublin. The President, Dr Donal de Buitleir, was in the Chair, and he held the first of two required votes on the proposed amendments to the Society`s Laws and Constitution.
Proceedings of the Statistical and Social Inquiry Society of Ireland - one hundred and sixty-second session: 2008/2009
Keywords: Proceedings; Statistical and Social Inquiry Society of Ireland; 314.15